Rancang Bangun Drone Quadcopter Tanpa Awak Penyiram Pupuk Tanaman - Cyntia Widiasari; Raja S. Agustinus Dulan Este (Jurnal Elektro dan Mesin Terapan, 2020)
Currently, the fertilization process is carried out by farmers is still classified as manual. This method forces directly contact with fertilizers, which are chemicals. Continuoulys contact can cause itching or irritation of the skin and can even cause an infection of the skin. Advances in technology have enabled humans to create quadcopters that can help the fertilization process. The quadcopter designed in this research is equipped with a motor pump that will activate the fertilizer sprinkling system. Arduino and LDR sensors function to make the quadcopter automatically spray fertilizer according to the predetermined Waypoint. The information received by the fs-ia6b receiver module will be processed by AMP Pro which will later control the quadcopter system. ESC (Electronic Speed ​​Controller) as motor speed control as well as supporting devices and devices such as a compass as directions and Mission Planner software to support automatic flying to the destination. The test results showed that the position error of spraying the appropriate fertilizer at a predetermined point turned out to have a shift in position. The point shift is 0.2 - 0.5 meters. The quadcopter can lift loads stably from 300-600 ml, with a battery capacity of 5500 mAH and a voltage of 22.2V. The quadcopter can fly without additional load for 10-15 minutes. When the 600 ml is added, the quadcopter can fly for about 7-8 minutes. Keywords: Fertilization, Quadcopter, AMP Pro, Waypoint, Mission Planner.